Prevalence and prognostic implications of increased apical basal strain ratio in aortic stenosis undergoing transcatheter aortic valve replacement. (25th November 2020) - Pedersen, A.L.D; Povlsen, J.A; Dybro, A; Clemmensen, T.S; Ladefoged, B; Poulsen, S.H
Abstract: Background: A substantial number of elderly patients with aortic stenosis (AS) have been reported to have coexisting transthyretin cardiac amyloidosis (ATTR). These patients are characterized by advanced heart failure symptoms and increased NTproBNP. Raising clinical suspicion of ATTR in AS patients seems difficult. Recent data has shown that an increased apical-basal strain ratio (ABr) derived by echocardiography predicts the diagnosis of cardiac amyloidosis (CA) in patients with left ventricular (LV) hypertrophy. However, the prevalence and prognostic value of ABr, a potential marker of ATTR, in patients with symptomatic AS undergoing transcatheter aortic valve replacement (TAVR) is unknown. The aim of this study was to investigate the preoperative prevalence, relation to symptoms and prognostic implications of elevated ABr in patients with symptomatic AS undergoing TAVR. Methods: We obtained data including survival status from 499 consecutive AS patients who underwent TAVR in the period 2016–2018 at our institution. From 2D echocardiographic apical images ABr was calculated as mean longitudinal strain of the 5 LV apical segments divided by the mean of the 6 LV basal segments. Patients were stratified according to ABr; 0–1.9 was considered normal, 2–2.9 mildly increased, 3.0–3.9 moderately increased and ≥4 severely increased. Results: Median follow-up time was 743 days. Mean age was 80±7 years. The prevalence of ABr ≥4 was 16% (n=78). These patients had higher preoperative NYHA class (77% were NYHA III or IV compared to 59% in ABr 0–1.9, p=0.003). Median preoperative NTproBNP levels for ABr ≥4 were 1781 pmol/l compared to 876 pmol/l in ABr 0–1.9 (p=0.003). NTproBNP levels decreased for all ABr subgroups at three months follow-up but remained considerably elevated in ABr ≥4 (median of ABr ≥4 was 1262 pmol/l compared to 645 pmol/l for ABr 0–1.9, p=0.001). LV ejection fraction (EF) in ABr 0–1.9 and ≥4 was 50% and 46%, p=0.014. The preoperative aortic valve stenosis severity derived by echo Doppler parameters were comparable across ABr subgroups. Overall, increased ABr ≥4 was associated with poor survival (fig. 1). In univariate analysis ABr ≥4 (HR 1.90, p=0.018), preoperative NTproBNP levels above the median of 1226 pmol/l (HR 3.14, p=0.003), increasing age (HR 1.05, p=0.018), TAPSE <19 mm (HR 1.91, p=0.011) and LV EF <50% (HR 1.60, p=0.045) were significant predictors of mortality. Preoperative NTproBNP >1226 pmol/l emerged as the only significant outcome predictor in a multivariate analysis (HR 2.67, p=0.029). Conclusion: Increased ABr ≥4 occurs frequently and is associated with significantly higher pre- and postoperative NYHA class, NTproBNP levels and reduced survival in symptomatic AS patients undergoing TAVR. Some of these patients might have undiagnosed CA. The echocardiographic derived ABr could in future studies prove to be a useful tool in raising suspicion of ATTR leading to referral for diagnostic testing for CA. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Danish Independent Research Fund